2019
DOI: 10.1021/acs.iecr.9b02697
|View full text |Cite
|
Sign up to set email alerts
|

Janus Particles with Varying Configurations for Emulsion Stabilization

Abstract: Analogous to molecular surfactants, amphiphilic Janus particles can function as surface active agents to stabilize emulsions. For molecular surfactants, the shape and amphiphilicity, described by packing parameters and hydrophilic−lipophilic balance (HLB), respectively, determine the type of emulsions that are produced. However, it remains unclear which features of Janus particles determine the type of emulsion that can be stabilized by these particles. In this study, a homologous series of amphiphilic Janus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Analytical calculations illustrated that by switching from a homogeneous particle of neutral wettability ( 10 nm, , ) to a highly amphiphilic Janus particle ( ), the desorption energy is increased by approximately three-fold [ 82 ]. Inspired by the potential of Janus particles at fluid interfaces and the tunability of their behavior, research has boomed in this area with applications spanning from enhanced oil recovery to bi-phasic catalytic reactions [ 6 , 89 , 90 , 118 , 119 ]. However, the rotational behavior of Janus particles cannot be neglected as the particle stability is also influenced by its orientation at the interface [ 78 , 107 , 120 , 121 , 122 , 123 , 124 ].…”
Section: Stability Of Particles At Fluid Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical calculations illustrated that by switching from a homogeneous particle of neutral wettability ( 10 nm, , ) to a highly amphiphilic Janus particle ( ), the desorption energy is increased by approximately three-fold [ 82 ]. Inspired by the potential of Janus particles at fluid interfaces and the tunability of their behavior, research has boomed in this area with applications spanning from enhanced oil recovery to bi-phasic catalytic reactions [ 6 , 89 , 90 , 118 , 119 ]. However, the rotational behavior of Janus particles cannot be neglected as the particle stability is also influenced by its orientation at the interface [ 78 , 107 , 120 , 121 , 122 , 123 , 124 ].…”
Section: Stability Of Particles At Fluid Interfacesmentioning
confidence: 99%
“…For instance, Ruhland et al synthesized Janus particles of different geometries using block terpolymers and reported that spherical Janus particles ( nm in diameter) reduce the toluene/water interfacial tension from mN/m to mN/m, whereas cylindrical Janus particles (diameter of nm and length of nm) can further decrease the tension down to mN/m [ 47 , 78 ]. The interfacial activity of Janus particles has been used to explain their superior performance in interfacial systems, such as their role as stabilizers in emulsions and foams, schematically shown in Figure 1 c [ 72 , 75 , 89 ]. As an example, Yin et al studied the impact of Janus character for nanofluids flooding in enhanced oil recovery and showed that utilizing Janus nanosheets at an ultralow concentration of wt.% reduces the oil/water tension and yields higher interfacial shear viscosity, which in turn can enhance the efficiency of oil recovery by more than 18% with minimal impairment to the permeability [ 90 ].…”
Section: Introductionmentioning
confidence: 99%
“…[81] By designing the Janus particles, shape-changeable and amphiphilicity-tunable colloidal surfactants are also developed, which could reverse the emulsion type under proper conditions, such as pH changes. [90,91,92] A well-known application of Janus dimer particles with asymmetric optical and magnetic properties is display. The motion of two-color Janus particles can be controlled remotely under the action of external electric or magnetic field.…”
Section: Applications Of Dimer Particlesmentioning
confidence: 99%
“…We successfully prepared amphiphilic dimer particles consisting of a hydrophobic PLA bulb and a hydrophilic shellac‐PEG bulb and demonstrated that by engineering the diameter ratio of the dimer particles, i. e. the ratio of the hydrophobic bulb to the hydrophilic bulb, the curvature of the water/oil interface could easily be tuned, thus giving a flexible control over the type of emulsions, as shown in Figure 5a [81] . By designing the Janus particles, shape‐changeable and amphiphilicity‐tunable colloidal surfactants are also developed, which could reverse the emulsion type under proper conditions, such as pH changes [90,91,92] …”
Section: Applicationsmentioning
confidence: 99%
“…To improve the emulsion stability, amphiphilic Janus particles with uneven surface wettability, for example, one side hydrophilic and the other hydrophobic, are preferred . The amphiphilic Janus particles have a strong propensity to accumulate and stay at the interface, thus showing better stability …”
Section: Figurementioning
confidence: 99%